Mixed Oxide Catalyst for the Oxidation of Glycerol to Lactic Acid: Influence of the Preparation Method and Calcination Temperature - Noraini Razali; Ahmad Zuhairi Abdullah (Universitas Gadjah Mada, 2020)
The selective oxidation reaction of glycerol to produce lactic acid is a high-temperature reaction, and requiring a catalyst with high thermal stability. The mixed metal oxide is one of the potential catalysts to be explored. In this study, prepared CaCe supported on ZrO2 catalyst with two preparation methods (co-precipitation and impregnation), and calcination temperatures (800 and 600 °C) were investigated. The oxidation reaction of glycerol to lactic acid was carried out at 250 °C for 2 h in a base-free condition using pure glycerol as a reactant. The catalysts were characterized using XRD, TGA, XPS, SEM and basicity test to evaluate and correlate the physical and chemical properties with their catalytic performance. It was found that the catalyst prepared by co-precipitation and calcined at 800 °C exhibited the highest catalytic performance. The high lactic acid yield of 38.8 and 95% glycerol conversion were achieved. The catalyst was successfully developed with sufficient porosity and high intensity of mixed metal structure that contributed to the desired high performance. Improvement in the basicity and formation of surface oxygen vacancies was attributed to cationic Ce4+/Ce3+ elements leading to the promotion of lactic acid yield and high glycerol conversion.